Analysis of Public Service Ethics in Population Administration (Case Study of Family Card Making Services at the Palu City Population and Civil Registration Service) - Mappatoba, Mustainah; Haryono, Dandan (Lafadz Jaya Publisher, 2023)
This research aims to analyze public service ethics in population administration, with a focus on the Palu City Population and Civil Registry Service. Problems such as long processing times, unclear procedures, discrimination, unreasonable fees, unresponsive services, poor document quality, non-transparency and corrupt practices in processing Family Cards are the background for this research. The research method used is qualitative with a descriptive approach. Data was collected through in-depth interviews, observation and document analysis. Informants were selected using a purposive sampling technique from various levels in the organizational hierarchy, service applicants, and people who had interacted with population administration. The research results show several important findings. Efficient use of public funds, separation between personal and office property, and implementation of a merit system in employee recruitment and promotion are important aspects that need to be improved. In addition, responsibility, professional standards and accountability in the use of public funds must be improved. Responsiveness to complaints, problems and aspirations of the community is also a key factor in improving public service ethics. It is hoped that this research can contribute to understanding and improving ethical practices of public services in population administration. The practical implications of this research include recommendations for improvements in procedures, policies, and better organizational culture to ensure public services that are more ethical and responsive to community needs.